Protriptyline treatment of sleep hypoxaemia in Duchenne muscular dystrophy. Issue 12 (December 1989) - Smith, P E; Edwards, R H; Calverley, P M
Abstract : Protriptyline 20 mg daily reduced the total time spent in rapid eye movement sleep in an open study in four subjects with Duchenne muscular dystrophy. Sleep related hypoxaemia and episodes of desaturation were reduced. Anticholinergic side effects were prominent, however, in these patients, precluding its use for regular treatment.